Manfaat Asuransi Usahatani Padi dalam Menanggulangi Risiko Usahatani Krama Subak di Kecamatan Penebel Kabupaten Tabanan - LUH WIWEKA LAKSMIYUNITA DEWI; I KETUT SUAMBA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Benefits of Rice Farming Insurance in Overcoming the Risk of Subak Member Farming in Penebel District, Tabanan Regency The AUTP (Rice Farming Insurance) program is one of the government's efforts to protect farmers from losses through financial risk mitigation. Subak members’ decision in Penebel Subdistrict to register as an AUTP participant from 2016 to 2018 indicated that farmers felt the benefits of the AUTP program. This study aimed to analyze the extent of the benefits of AUTP in overcoming the risks of subak member farming and find out the response of subak member farmers to AUTP in Penebel District, Tabanan Regency. The study was conducted on Subak Keloncing, Subak Penatahan, and Subak Buruan with a sample of 65 farmers who received claimfunds. The data were analyzed employingquantitative and qualitative-descriptiveanalysis. The results showed that the percentage ratio of claims funds with production costs per 0.1517 ha amounted to 124.18% or more than 100%, meaning that the claim fundsfrom AUTP were able to overcome losses caused by pests, diseases, and drought. Whereas the farmers' response to the AUTP program measured through the attitude approach generally showed agreement but there were some farmers who argued that it was necessary to evaluate the AUTP program, especially in the claim submission mechanism. Based on the results of the study, it can be suggested to subak that the AUTP program needs to be developed and implemented. To the government, it is recommended that improvements to the implementation of AUTP be implemented, namely the damage below 75% can continue to follow the AUTP program with the amount of premiums and claims that are adjusted to the level of damage.